Pengaruh regulasi emosi kognitif terhadap depresi pada mahasiswa tingkat akhir dimasa pandemi covid-19 - Vira Qoyyum Maslita; Putri Saraswati; Udi Rosida Hijrianti (Fakultas Psikologi, 2021)
The COVID-19 pandemic has affected people’s mental health, especially in the education sector. One of the mental health problems that often occur in students who are completing their final assignments are symptoms of depression. Cognitive emotion regulation is one capacity to overcome depression with the use of adaptive approach. The purpose of this study was to determine the effect of cognitive emotion regulation on depression in final year students in Indonesia during the covid-19 pandemic. This study uses a quantitative approach. The research subjects were 349 final year students and their data were taken using an accidental sampling technique. Analysis of research data used the simple linear regression test. The results showed that there was a significant influence between cognitive emotion regulation and depression (p = 0.00). The effect of cognitive emotion regulation shown is 4.2% of the variance of depression. Keywords: Cognitive emotion regulation, college students, covid-19, depression, final assignment